Beyond sex roles what the Bible says about a woman's place in church and family - Bilezikian, Gilbert (Grand Rapids, MI Baker, 1985)
Includes bibliographical references and index.
Keywords: Women clergy -- biblical teaching; Women in church work -- biblical teaching; Women -- conduct of life -- biblical teaching; Women -- family life